PENDIDIKAN KARAKTER: KAJIAN HISTORIS HIERARKI PENDIDIKAN IMAM MUHAMMAD ABU ZAHRA - Noorzeha, Fuad; Sutono, Agus (FPIPSKR Universitas PGRI Semarang, 2023)
Many character education programs in Indonesia are carried out with various efforts through curriculum improvements from year to year. In addition to being a milestone in the success of education, character education is also carried out to prepare the nation's leaders. However, moral degradation is a challenge faced by the Indonesian nation today. Thus, character education in Indonesia is the main goal in the design of national education. The researcher describes the concept of character education of Imam Muhammad Abu Zahra through three hierarchies, namely; First. The period of structuring the human person. Second, the emphasis on the interest of prospective students. Third, deepening and specializing in the interests of student talents. Then, in addition to these three hierarchies, there are also four educational processes, namely; Spirit education, body education, Akhlaq education, and Aqliyah education. According to researchers, this concept can contribute to character education in Indonesia in the future.